Occupational exposures to bloodborne pathogens and its underreporting in dental teaching environment in an Indian dental school - Nilesh V Joshi; Mridula Joshi; Varsha Rathod; Deepak Langde (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aims of this study were 1) to find out the prevalence of occupational exposures to contaminated biological material among undergraduate students and interns; 2) to find out how many cases of occupational exposures to bloodborne pathogens are reported; and 3) to know the reasons for non-reporting of occupational exposures. Materials and Methods: The study was conducted in a Dental School in Navi-Mumbai, India. An anonymous self-administered questionnaire was formulated. 210 dental students were given a questionnaire out of which 150 students attending clinical postings in their third year, final year, and internship responded. Approval was obtained from the Institutional Ethical Committee. Results: The study revealed a very high prevalence (66.7%) of exposures among the students. Only 12% of the students reported the exposures to the staff. Students from III year and final year BDS (Bachelor of Dental Surgery) had mean exposure of 2.40 as compared to 1.94 among interns. 46% of the students stated that they did not report about the exposure because they thought that injury was of minor nature. Conclusion: There is a very high prevalence of occupational exposures among students which are not reported. There is a need for the development of a post exposure protocol which has to be strictly implemented. The principle of infection control has to be emphasised to the students periodically and they should be encouraged to report incidences of exposures to biological material.